Plasmodium yoelii inhibitor of cysteine proteases is exported to exomembrane structures and interacts with yoelipain-2 during asexual blood stage development - Pei, Ying (2013)
Plasmodium falciparum (Pf) blood stages express falstatin, an inhibitor of cysteine proteases (ICP), which is implicated in regulating proteolysis during red blood cell infection. Recent data using the Plasmodium berghei rodent malaria model suggested an additional role for ICP in the infection of hepatocytes by sporozoites and during liver stage development. Here we further characterize the role of ICP in vivo during infection with Plasmodium yoelii (Py) and Pf. We found that Py-ICP was refractory to targeted gene deletion indicating an essential function during asexual blood stage replication, but significant down-regulation of ICP using a regulated system did not impact blood stage growth. Py-ICP localized to vesicles within the asexual blood stage parasite cytoplasm, the parasitophorous vacuole, and was exported to dynamic exomembrane structures in the infected erythrocyte. In sporozoites, expression was observed in rhoptries, in addition to intracellular vesicles distinct from TRAP containing micronemes. During liver stage development, Py-ICP was confined to the parasite compartment until the final phase of liver stage development when, after parasitophorous vacuole membrane breakdown, it was released into the infected hepatocyte. Finally, we identified the cysteine protease yoelipain-2 as a binding partner of Py-ICP during blood stage infection. These data show that ICP may be important in regulating proteolytic processes during blood stage development, and is likely playing a role in liver stage-hepatocyte interactions at the time of exoerythrocytic merozoite release.